2000
DOI: 10.1111/j.1532-950x.2000.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Compacted Cancellous Bone Grafting on the Healing of Subchondral Bone Defects of the Medial Femoral Condyle in Horses

Abstract: Cartilage healing is similar in grafted and ungrafted defects in the equine medial femoral condyle at 6 months, suggesting that surgical debridement alone of cystic structures remains the treatment of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 33 publications
2
36
0
1
Order By: Relevance
“…Cancellous bone grafting of the medial femoral condyle (MFC) was characterised by the presence of dead graft and secondary cyst formation compared to ungrafted defects which were filled with fibrous tissue without identifiable cyst formation (Jackson et al, 2000).…”
mentioning
confidence: 99%
“…Cancellous bone grafting of the medial femoral condyle (MFC) was characterised by the presence of dead graft and secondary cyst formation compared to ungrafted defects which were filled with fibrous tissue without identifiable cyst formation (Jackson et al, 2000).…”
mentioning
confidence: 99%
“…The positive results could be attributed to the omitted membrane and the different biomechanical loading of articular cartilage at the concave trochlear groove compared to the convex femoral condyle. However, on the basis of this study, and in agreement with Jackson et al (2000), filling subchondral defects with compacted cancellous bone in weight-bearing joint surfaces cannot be recommended.…”
Section: Article In Pressmentioning
confidence: 46%
“…Eight of the 10 cases were considered to make a satisfactory clinical recovery. More recently an experimental study examining the effect of compacted cancellous bone grafting in the healing of experimental subchondral bone defects (12.7 mm diameter and 19 mm deep) in the MFC concluded that there was no significant difference between grafted and ungrafted defects with respect to lameness, radiographic score or percent bone fill (Jackson et al 2000). Histologically grafted defects were characterized by the presence of dead graft and secondary cyst formation in 4 defects.…”
Section: Treatmentmentioning
confidence: 99%
“…Ungrafted defects filled with fibrous tissue and no cyst formation was identified. The author has never used cancellous bone grafts in the treatment of SCLs based on an initial apprehension of bone graft getting into the femorotibial joint, but based on both anecdotal experience, as well as the paper of Jackson et al (2000), there appears to be little support for continued use of this technique.…”
Section: Treatmentmentioning
confidence: 99%